Spectroscopic Study of 39Ca for Endpoint Nucleosynthesis in Classical Novae. (October 2020) - Liang, J; Chen, A A; Anger, M; Bishop, S; Faestermann, T; Fry, C; Hertenberger, R; Psaltis, A; Seiler, D; Tiwari, P; Wirth, H-F; Wrede, C
Abstract: Classical novae are environments which can produce heavier elements up to mass A ∼ 40. These nuclides at the endpoint of nova nucleosynthesis consist of elements such as Ar, K, and Ca. There is an order of magnitude discrepancy with the predicted and theoretical abundances of these endpoint nuclides produced in a classical nova. The uncertainty in the theoretical 38 K(p, γ) 39 Ca reaction rate has been shown to affect the abundances by an order of magnitude or more. The only direct measurement of this reaction rate was performed with the DRAGON facility at TRIUMF; however additional spectroscopic data could aid the interpretation of this data as well as motivate further study of this reaction rate. In this study, we present the preliminary results of a spectroscopic study of 39 Ca using the 40 Ca(d, t) 39 Ca reaction carried out at the Maier-Leibnitz Laboratory in Garching, Germany.